The importance of the geopolitical location of Yemen and Somalia and their impact on Arab security - Ali, Ahmed Khalil (Journal of natural sciences, life and applied sciences, 2021)
It occupies the Yemen Arab Republic, the Republic of Somalia geographical area strategy and is located on the Red Sea entrance to the southwest of the Arabian Peninsula for Yemen and South Horn of Africa for Somalia and a surface area of ​​about two hundred thousand square kilometers, which is in this way, more like the box ever great strategic importance in the chessboard the Middle East region. Yemen and Somalia's recent history, began on the shores of the Red Sea, while the evacuation of Turks from Yemen in 1919 and the Declaration of Independence of the Republic of Somalia until the conflict broke out between the clans civil where these tribes were announced after its agreement to declare its political stabilits.This period, which lasted until the establishment of the Arab League in 1945, a dispute between the three camps, vying for the leadership of the Arab world has seen, namely: the Hashemites camp who are concentrated in Jordan, Iraq, and Camp Saudis who parcels Hashemites of the peninsula, and the camp of the Egyptians who had begun showing some interest Arab affairs. Yemen and Somalia have Anzmt to the League of Arab StatesThe context of the events and indications in the political and economic scene in Yemen and Somalia is moving towards escalation addition overshadowed by the context of the crisis on the Arab arena, helped by the absence of future strategies that the major and important events, dominated the thought of permanence Ostmraraharb against change without analytical reading closer to the reality of the local strategic environment and regional and international Vtozmt data Which contributed to the accumulation of political, economic, social, educational, health, security and other problems in the context of crises warring tribes Under palaces strategic perspective and geostrategic, limited resources, and weak of will and national administration toward reform, as well as the form of violence to the weakness of economic power and political instability that arrived in an anonymous way for the future of Yemen and Somalia so has to be the future vision analysis according to data transformations and changes geostrategic theater Yemen and Somalia, from the consequences up to the expectations and the current implications in the strategic landscape of Yemen and Somalia are the secretions of a cumulative political, ideological, social, security, ethnic, tribal, regional, factional and spatial different in Yemen and Somalia, for this to spectra to be analytical vision for the future of Arab countries about the national security of Yemen and Somalia for political and economic stability to both countries. this means safe for the Arab States.
Keywords: geopolitical site; Yemen; Somalia; Arab security